Pattern of households' savings: a tale of two surveys - Buragohain, T. and Das, S.K. (The India Journal of Economics)
This paper attempts to assess the households$1 (Bsavings behavior from two sets of nationality representative penal data- IHDS -1 and IHDS-II ( India Human development survey). The study finds that each income quintile is not a homogeneous grope. Among top income quintiles, there are households whose expenditure exceeds income. The study funds that households$1 (Bincome is the major determinants of consumption expenditure and savings. The estimated marginal propensity to spend on consumption lies between zero and one among all quintiles. Hence, the satisfied the Keynesian hypothesis with recent primary households$1 (Bdata. - Reproduceds
Keywords: Income, Marginal income